A review of the “metallome” within neurons and glia, as revealed by elemental mapping of brain tissue - Gaewyn Ellison; Ashley L. Hollings; Mark J. Hackett (BBA Advances, 2022)
It is now well established that transition metals, such as Iron (Fe), Copper (Cu), and Zinc (Zn) are necessary for healthy brain function. Although Fe, Cu, and Zn are essential to the brain, imbalances in the amount, distribution, or chemical form (“metallome”) of these metals is linked to the pathology of numerous brain diseases or disorders. Despite the known importance of metal ions for both brain health and disease, the metallome that exists within specific types of brain cells is yet to be fully characterised. The aim of this mini-review is to present an overview of the current knowledge of the metallome found within specific brain cells (oligodendrocytes, astrocytes, microglia, and neurons), as revealed by direct elemental mapping techniques. It is hoped this review will foster continued research using direct elemental mapping techniques to fully characterise the brain cell metallome.